Plato and the sea (Revista Archai, 2020)
How is Plato facing the sea? A complex vision emerges from the reading of his dialogues. It touches on various fields of his reflections. Plato feels its fascination and at the same time feels its dangers, not only those connected to navigation, but also the moral ones, the ones deriving from the presence in the ports of men of various origins, mostly with vulgar and foul-mouthed attitudes; and then those related to the wealth of the assets accumulated in them, with the necessary and consequent corruption of habits. It seems that in Plato, on the one hand, there is a nostalgia for the past, when the city was small, and life was simple, fundamentally linked to agriculture, with few needs. But on the other hand, and at the same time, he is well aware that maritime trade is now closely linked to the growth and evolution of the city, and devises a series of measures aimed at containing those dangers. Plato talks about all this, and more, in his unique and inimitable "style", mixing logical reasoning with metaphors, analogies, images (some of which are beautiful and poetic). One of the most beautiful metaphors, developed in a series of original considerations, is the one between the sea and discourse: the sea is like discourse, or, if you want, the discourse is like the sea, full of dangers but absolutely indispensable for life in common among men.